2010
DOI: 10.1007/s13225-009-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic mycobiota of leaves and roots of the grass Holcus lanatus

Abstract: Holcus lanatus is a grass that grows in humid, often waterlogged soils in temperate zones around the world. The purpose of this work was to identify fungal endophytes associated with its roots and leaves, and to describe the diversity and spatial distribution patterns found in its mycobiota. Holcus plants were sampled at 11 locations in western and northern Spain, and endophytes were isolated from leaves and roots of each plant. Morphological and molecular methods based on the ITS1-5.8SrRNA-ITS2 sequence were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 29 publications
10
71
2
1
Order By: Relevance
“…Previous studies in other plants have also indicated that endophytes exhibit tissues specificity [58], [59], [60]. As expected, tissue specificity of fungal endophytes was demonstrated in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in other plants have also indicated that endophytes exhibit tissues specificity [58], [59], [60]. As expected, tissue specificity of fungal endophytes was demonstrated in our study.…”
Section: Discussionsupporting
confidence: 92%
“…However, since "morphotype" concept was defined (Hawksworth et al 1995), cultural characteristics of fungi are helpful as complementary data for the molecular identification (Guo et al 2003;Lacap et al 2003). Phylogenetic analysis of morphospecies has been increasingly used in the identification for endophytic fungi (Huang et al 2006;Albrectsen et al 2010;Pinruan et al 2010;Sánchez Márquez et al 2010), however there are also problems with this methodology. Many taxa can only be identified to family level as no similar sequences can be blasted in GenBank (Cai et al 2009;Pinruan et al 2010), while identification is based on blasting with a similar sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Beside mycorrhizal fungi, a growing number of published studies of fungal communities associated with plant roots indicate a significant presence of endophytes (Porras-Alfaro et al 2008;Hyde and Soytong 2008;Sánchez Márquez et al 2010). These fungi inhabit the apoplastic spaces of their plant hosts and can colonize the roots of all plant species (Arnold 2007;Rodriguez et al 2009).…”
Section: Introductionmentioning
confidence: 99%